Laryngeal reconstruction for recurrent desmoid tumor using three‐dimensional modeling: A unique approach for a rare tumor. (25th December 2018) - Tracy, Lauren F.; Patel, Samip N.; Buckmire, Robert A.; Shah, Rupali N.
Abstract : Desmoid tumors are exceedingly rare within the larynx and cause significant morbidity due to their locally aggressive and infiltrative nature. Surgery is the mainstay of treatment with previous reports describing total and near‐total laryngectomy for cure. We present a case of recurrent glottic desmoid tumor managed with hemilaryngectomy and reconstructed with temporoparietal free tissue, rib, and buccal grafts. Three‐dimensional modeling was utilized to optimize aerodigestive function after laryngeal reconstruction. Laryngoscope, 129:1989–1992, 2019